The Used Of Translation Techniques By Donna Widjajanto In Tranlating CSI’s In Dterlizzi’s The Field Guide - Setiawan, Kurnia Ari (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
The goal of the study is to know the implementation of translation techniques are used by the translator. This research design uses descriptive qualitative research approach. Meanwhile, the findings of this research show that 9 translation techniques were applied in the book 1 “The Field Guide” in rendering 69 words which are classified to CSI’s. Translator borrowed the source language terms (pure borrowing and naturalized borrowing) majority applied by the translator which is used to translate terms in anthroponyms, belief and religion concepts, ecology. The translator expected to SL oriented in the execution of translation techniques in rendering culture-specific items in The Field Guide book. Dealing with back translation, translator intends to prevent the culture-specific items in source language. To achieve balance, the translator should decrease in taking the originality of source language words into target language words and prevent the use of strange cultural terminologies.